How Does a Ceramic Melt Under Laser? Tunnel Ionization Dominant Femtosecond Ultrafast Melting in Magnesium Oxide - Hui Zhao; Shiqi Hu; Mengxue Guan; Xinbao Liu; Daqiang Chen; Jiyu Xu; Sheng Meng (Ultrafast Science)
Laser-induced melting plays a crucial role in advanced manufacturing technology and ultrafast science; however, its atomic processes and microscopic mechanisms, especially in a wide-gap ceramic, remain elusive due to complex interplays between many degrees of freedom within a timescale of ~100 fs. We report here that laser melting is greatly accelerated by intense laser-induced tunnel ionization, instead of a priori multiphoton absorption, in the archetypal ceramic magnesium oxide (MgO). The tunneling processes generate a large number of photocarriers and results in intense energy absorption, instantaneously altering the potential energy surface of lattice configuration. The strong electron–phonon couplings and fast carrier relaxation enable efficient energy transfer between electrons and the lattice. These results account well for the latest ultrafast melting experiments and provide atomistic details and nonequilibrium mechanism of photoinduced ultrafast phase transitions in wide-gap materials. The laser modulation of melting thresholds and phase boundary demonstrate the possibility of manipulating phase transition on demand. A shock wave curve is also obtained at moderate conditions (P = 2 GPa), extending Hugoniot curve to new regimes.